2023
DOI: 10.1111/myc.13589
|View full text |Cite
|
Sign up to set email alerts
|

A contemporary investigation of burden and natural history of aspergillosis in people living with HIV/AIDS

Abstract: Background: Untreated HIV infection can lead to profound immunosuppression and increase susceptibility of people living with HIV/AIDS (PLHA) to aspergillosis.Objectives: Reporting the burden and natural history of aspergillosis documented in PLHA admitted in five medical centres in Brazil.Patients and Methods: Clinical, epidemiological and laboratory data were collected in all sequential cases of proven or probable aspergillosis documented in PLHA hospitalised in five medical centres between 2012 and 2020. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…In Brazil, mortality of 73% was reported in a retrospective review of outcomes of 11 severely immunocompromised people with HIV and invasive aspergillosis. 26 In South Africa, people with HIV admitted to hospital with candidaemia had almost twice the risk of mortality compared with HIV-seronegative patients. 27 …”
Section: Other Invasive Fungal Pathogensmentioning
confidence: 99%
“…In Brazil, mortality of 73% was reported in a retrospective review of outcomes of 11 severely immunocompromised people with HIV and invasive aspergillosis. 26 In South Africa, people with HIV admitted to hospital with candidaemia had almost twice the risk of mortality compared with HIV-seronegative patients. 27 …”
Section: Other Invasive Fungal Pathogensmentioning
confidence: 99%
“…Men who have sex with their fellow men (MSM) are at high risk of developing AIDS [1]. Clinical studies have found that in recent years, the incidence of AIDS in high-risk male groups in China has slowly been showing an increasing trend and the proportion of newly diagnosed patients among high risk groups is also increasing every year [2,3]. In addition, men who have sex with their fellow men and are around 20 to 25 years of age, have relatively weak health awareness but have high sexual activities hence, leading to a greater risk of developing AIDS and other diseases due to compromised body immunity [4,5].…”
Section: Introductionmentioning
confidence: 99%